1999
DOI: 10.1016/s0741-5214(99)70348-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative predictors of colonic ischemia after ruptured abdominal aortic aneurysm

Abstract: The results of this study show that: (1) colonic ischemia after rAAA may be predicted with the presence of two or more specific perioperative factors, (2) the lack of a guaiac-positive bowel movement may be misleading for the early diagnosis of colonic ischemia, and (3) more than 50% of the patients with colonic ischemia will require a colonic resection. We recommend that any patient with rAAA with more than two perioperative factors undergo sigmoidoscopy every 12 hours after surgery for 48 hours to rule out c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
3
32
3
Order By: Relevance
“…(1.13-20.32)) were reported as risk factors in one study [20] . Pre-operative renal impairment was identified as a significant risk factor for development of ischaemic colitis in two papers, with reported odds ratios of 2.30 [14] and 4.67 [10] .…”
Section: Pre-operative Factorsmentioning
confidence: 90%
See 1 more Smart Citation
“…(1.13-20.32)) were reported as risk factors in one study [20] . Pre-operative renal impairment was identified as a significant risk factor for development of ischaemic colitis in two papers, with reported odds ratios of 2.30 [14] and 4.67 [10] .…”
Section: Pre-operative Factorsmentioning
confidence: 90%
“…Dadian et al identified intra-operative hypotension of <70mmHg as associated with IC [19] . Three studies identified that massive transfusion was associated with increased rates of IC [19,20,15] . All of these were retrospective singlecentre observational studies.…”
Section: Pre-operative Factorsmentioning
confidence: 99%
“…Indication for surgical decompression was based on an IVP Ͼ20 mm Hg or abdominal perfusion pressure (systemic mean pressure minus intra-abdominal pressure) of Ͻ50 to 60 mm Hg and new development of organ dysfunction, or when patients fulfilled at least one of the criteria from the Table. 9,[15][16][17] The general algorithm of OAT for all RAAA patients in our institution is illustrated in Patients treated by eEVAR are at high risk for development of ACS; therefore, close monitoring of IVP and organ function is crucial to detect critical IAH. IVP measurement is initiated during EVAR and repeated every hour after the procedure.…”
Section: Patientsmentioning
confidence: 99%
“…Trauma victims suffer acute intestinal ischemia from direct mesenteric vessel injury or hemorrhagic shock [4 -6]. Surgical patients undergoing aortic or cardiac surgery involving bypass and/or aortic cross-clamping are shown to be at higher risk for intestinal ischemia complications postoperatively [7][8][9]. The mortality of patients with intestinal ischemia remains high, often due to the associated development of the systemic inflammatory response syndrome (SIRS) [10 -14].…”
Section: Introductionmentioning
confidence: 99%